Percutaneous spinal cord stimulation cylindrical lead placement for managing refractory neuropathic pain: A case series with an endoscopic-assisted approach - Zhouyang Hu; Hong Wang; Zhipeng Xu; Jianjin Zhang; Lijun Li; Guoxin Fan; Xiang Liao (Journal of Central Nervous System Disease)
Background The paddle lead (PL) and cylindrical lead (CL) remain the main implant categories in spinal cord stimulation (SCS) for treating neuropathic pain. Surgeons often complain about the greater trauma associated with PL implantation, while percutaneous endoscopic technique offers a promising approach for minimizing the trauma associated to PL implantation. However, there remains a dearth of real-world case study on endoscopy-assisted CL implantation. Purpose This study aimed to demonstrate the endoscopic-assisted approach and outcomes of CL implantation in SCS for managing neuropathic pain. Research Design A retrospective case series. Study Sample Patients aged 18 years and above with chronic neuropathic pain persisting for at least three months, refractory to standardized conservative treatment, were enrolled between January 2021 and March 2023. Data Collection and Analysis The surgical key steps including puncture, working cannula placement, endoscopic laminotomy and endoscopic CL introduction were demonstrated. Characteristics as demographics, follow-up time, visual analog scale (VAS) score, pain disability index (PDI) score and patient-reported outcomes measurement information system (PROMIS) scale were assessed. Results Successful CL implantation under endoscopy was achieved in all patients, including 3 with failed back surgery syndrome, 2 with complex regional pain syndrome and 2 with chronic pelvic pain. No spinal cord injuries, dural tears, lead migration, lead fractures, or postoperative infections were observed. VAS score of regional pain, PDI score as well as PROMIS of patient’s quality of life were all significantly improved after surgery. Conclusion Percutaneous endoscope-assisted CL implantation offered a new alternative technique for SCS in managing neuropathic pain.